DIGITALIZATION AND MARKETING AS TWO SIDES OF THE SAME MEDAL - THE ROAD OF TRANSFORMATION IN THE REPUBLIC OF SERBIA - Алексић, Ивана; Tripkovic, Anđelka (Economic Outlook, 2023)
In the XXI century -the era of digitization, quick and unpredictable changes included marketing as a social and management process. Namely, it is about the transformation of the traditional into a digital form of marketing (Marketing 4.0). Although the path of transition shows that walking on the beaten track can lead to the achievement of goals (traditional marketing), it seems that in the world of technology, presence and advertising on the Internet (digital marketing) are conditions and thus a guarantee for efficient and effective results. In this respect, the subject of this paper is the analysis of the consequences of digitalization on the marketing process, with special reference to their connection and mutual conditioning. The aim of this paper is to point out the possibilities, techniques, and advantages of the use of digital marketing, including an analysis of the changes that characterize the mentioned sector in the Republic of Serbia.  This paper begins with a basic hypothesis that the application of digital technologies in marketing is not only an available opportunity and a question of choosing "yes or no", but a necessity in the development and implementation of marketing strategies and thus in achieving recognition and competitive advantage in the market.
Keywords: digital marketing; the Republic of Serbia; online marketing; mobile marketing; electronic commerce